THE RISK ASSESMENT AND IMPACT OF HYGIENIC CONDITIONS ON THE DEVELOPMENT OF LEGIONELLA SPP. IN WATER SYSTEMS OF PUBLIC AND TOURIST FACILITIES - Bešić, Adna; Obradović, Zarema; Dautbegović, Adisa; Obradović, Amina (International Journal of Research -GRANTHAALAYAH, 2017)
A large number of different diseases are associated with the consumption of hygienic defective water and the use of water for maintaining personal hygiene. Recreational waters, water in systems intended for cooling and heating of public buildings are also significant. Among these diseases, the most significant is legionellosis, the disease which has become more and more important in the whole world in recent years. The aim of this paper was to evaluate the connection of hygienic conditions in public buildings with the appearance of genus Legionella in drinking and bathing water, as well as water from outside and inside fountains, pools and water from cooling and heating systems for public buildings. Obtained results are also used to evaluate the risk of developing legionellosis in the population of Bosnia and Herzegovina and among foreign tourists. The presence of Legionella spp. was analysed in 238 samples of water taken from faucets in rooms of buildings intended for people's accommodation, in open and closed fountains, pools, cooling and water systems. Hygienic conditions in the facilities were assessed using survey questionnaire and complemented with legionella findings. This study showed the direct correlation between hygienic conditions in public and tourist facilities with the presence of Legionella spp. in the waters taken in these objects.